UNCONVENTIONAL GAS RESOURCES IN THE EASTEN PETROLEUM REGION OF UKRAINE - Vakarchuk, S.; Dovzhok, T.; Kharchenko, M.; Filyushkin, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Unconventional gas prospects for Ukraine are mostly linked to the eastern petroleum region. The research into unconventional resources reveals shale gas, siltstone and sandstone tight gas, and carbonaceous shale gas to be most perspective in the region. Based on the criteria laid down, there were determined main stratigraphic sequences prospective to accumulate unconventional gas. Eleven most productive shale gas strata are indentified for the Upper, Middle and Lower Carboniferous as well as for the Upper Devonian sedimentary rocks. Nine strata in the same series were recognized to be most effective for tight gas accumulations in clastic rocks. The Lower Tournaisian and Lower Visean strata are perspective to accumulate gas in the massive carbonate rocks. There have been determined most perspective exploration plays and areas within the Eastern petroleum region for each type of unconventional gas. Preliminary estimated recoverable resources of unconventional gas in the Eastern petroleum region total 19.5 bln m3.
Keywords: unconventional gas; shale gas; tight gas